The Value of Decentralisation in Wastewater Management: Gauteng Province Case Study, South Africa - Reynders, Cornelius Chris; Musiyarira, Harmony; Marjanovic, Prvoslav (Journal of Economic Development, Environment and People, 2012)
In a semi-arid water scarce country like South Africa, the efficient use of limited water resources and measures to extend the service value of these resources is a prerequisite for achieving sustainable development. The conventional supply-sided management approach to water supply causes increased wastewater generation with accompanied increased pollution loads requiring higher levels of mitigation environmental pollution. Where disposal of wastewater treatment effluent takes place in rivers and natural water bodies, the lack of adequate natural compensating capacity of such water bodies typically result in severe ecological damage of the aquatic environment. With a shift of emphasis to a sustainable demand side management approach (as opposed to a supply side one), the avoidance of water wastage and high wastewater generation represents both resource conservation and environmental protection friendly approaches and contribute to overall sustainability. The integrated nature of water supply and wastewater management systems require an approach that considers these systems holistically. A new paradigm for water management is therefore needed to ensure that the issues of waste disposal and pollution are dealt with in a sustainable manner taking into account the emerging objectives of modern society for resource conservation and environmental protection. A balance therefore has to be found between the uses of additional fresh water resources as a means of satisfying en ever increasing water demand on the one hand and alternative unconventional resource exploration and employment, without the risk of depletion of natural available fresh water resource flow, irreversible harm to the environment and social and economic constraints. This paper explores wastewater and grey water reuse as unconventional resources in a qualitative manner within this balancing equation. It further proposes a methodology for deriving monetary indicator values for wastewater reuse by internalising negative environmental impacts. This is achieved through application of Lagrangian optimisation of the treatment plant production function (output distance function) for deriving marginal prices of contaminant removal and resulting avoided pollution.